Transfer pricing in international business a management tool for adding value - Turner, Geoff. (2013 digital library., 2013)
Trade is understood to have taken place throughout much of recorded history. From those early beginnings, and through all the stumbling blocks, mistakes, and moments of inspiration over the centuries, the development of trade has contributed to the modern, globalized world in which we live. The increasing economic, social, and political importance of trade spawned a phenomenon called the multinational organization. These organizations are capable of exercising extreme power not only in individual countries but globally for they are a source of revenue, employment, and economic activity. However, these organizations have a national home where profits will ultimately have to come, and in their effort to maximize the amount repatriated, they often engage in internal-pricing practices, known more commonly as transfer pricing, which enrage either their host or home countries, provoking them to monitor and capriciously modify transfer prices as a way of protecting their national income.